A Brain Signaling Framework for Stress-Induced Depression and Ketamine Treatment Elucidated by Phosphoproteomics - Xiao, Yan; Luo, Huoqing; Yang, Wen Z.; Zeng, Yeting; Shen, Yinbo; Ni, Xinyan; Shi, Zhaomei; Zhong, Jun; Liang, Ziqi; Fu, Xiaoyu; Tu, Hongqing; Sun, Wenzhi; et al. (Frontiers in Cellular Neuroscience, 2020)
Depression is a common affective disorder characterized by significant and persistent low mood. Ketamine, an N-methyl-D-aspartate receptor (NMDAR) antagonist, is reported to have a rapid and durable antidepressant effect, but the mechanisms are unclear. Protein phosphorylation is a post-translational modification that plays a crucial role in cell signaling. Thus, we present a phosphoproteomics approach to investigate the mechanisms underlying stress-induced depression and the rapid antidepressant effect of ketamine in mice. We analyzed the phosphoprotein changes induced by chronic unpredictable mild stress (CUMS) and ketamine treatment in two known mood control centers, the medial prefrontal cortex (mPFC) and the nucleus accumbens (NAc). We initially obtained > 8000 phosphorylation sites. Quantitation revealed 3988 sites from the mPFC and 3196 sites from the NAc. Further analysis revealed that changes in synaptic transmission-related signaling are a common feature. Notably, CUMS-induced changes were reversed by ketamine treatment, as shown by the analysis of commonly altered sites. Ketamine also induced specific changes, such as alterations in synapse organization, synaptic transmission, and enzyme binding. Collectively, our findings establish a signaling framework for stress-induced depression and the rapid antidepressant effect of ketamine.